Highly prevalent V600E and low-frequency promoter mutations underlie papillary thyroid carcinoma in Koreans - Sue Youn Kim; Taeeun Kim; Kwangsoon Kim; Ja Seong Bae; Jeong Soo Kim; Chan Kwon Jung (Korean Society of Pathologists & the Korean Society for Cytopathology, 2020)
Background The presence of telomerase reverse transcriptase (TERT) promoter mutations have been associated with a poor prognosis in patients with papillary thyroid carcinomas (PTC). The frequency of TERT promoter mutations varies widely depending on the population and the nature of the study. Methods Data were prospectively collected in 724 consecutive patients who underwent thyroidectomy for PTC from 2018 to 2019. Molecular testing for BRAF V600E and TERT promoter mutations was performed in all cases. Results TERT promoter alterations in two hotspots (C228T and C250T) and C216T were found in 16 (2.2%) and 4 (0.6%) of all PTCs, respectively. The hotspot mutations were significantly associated with older age at diagnosis, larger tumor size, extrathyroidal extension, higher pathologic T category, lateral lymph node metastasis, and higher American Thyroid Association recurrence risk. The patients with C216T variant were younger and had a lower American Thyroid Association recurrence risk than those with hotspot mutations. Concurrent BRAF V600E was found in 19 of 20 cases with TERT promoter mutations. Of 518 microcarcinomas measuring ≤1.0 cm in size, hotspot mutations and C216T variants were detected in five (1.0%) and three (0.6%) cases, respectively. Conclusions Our study indicates a low frequency of TERT promoter mutations in Korean patients with PTC and supports previous findings that TERT promoter mutations are more common in older patients with unfavorable clinicopathologic features and BRAF V600E. TERT promoter mutations in patients with microcarcinoma are uncommon and may have a limited role in risk stratification. The C216T variant seems to have no clinicopathologic effect on PTC.